Assistencialismo e protagonismo infantil: o movimento das práticas pedagógicas construídas na EMEI Professora Ida Fiori Druck - Maia, Adriana Turchiello (2020)
This Dissertation is part of the Research Line (LP2) - Pedagogical Management and Educational Contexts of the Professional Master's Course in Public Policies and Educational Management at the Federal University of Santa Maria (RS). Its theme is the pedagogical practices developed in Early Childhood Education and narratives. The objective is to understand the process of constitution of the pedagogical proposal of the Municipal School of Early Childhood Education Professor Ida Fiori Druck. The research has a qualitative approach (GATTI, 2002; MINAYO, 2015), through narrative research (CLANDININ and CONNELLY 2015), and the data was obtained through documentary analysis (LUDKE and ANDRÉ 1986), in the Pedagogical Political Projects, school files and other documents such as photographs and minutes. Semi-structured interviews were conducted (MINAYO, 2009) with the management team, teachers and employees. The theoretical foundations result from a survey of public policies regarding early childhood education in Brazil and in the municipality of Santa Maria R / S. The official national documents revisited were: the Constitution of the Federative Republic of Brazil (1988), ECA (1990), LDBEN, Law Nº 9.394 / 96, RCNEI (1998), DCNEI (2010), the two National Plans of Education (PNE), (2001-2011) and (2014-2024), and BNCC (2017), RCG (2018) and DOC (2019). In the documental analysis several moments of constitution of the pedagogical practices were revisited, that the EMEI traced in its almost 40 years, emerged primarily as an assistance and later as educational space, having over the years the caring and education inseparable. We found that EMEI understands that pedagogical practices change over time and according to the opportunities for continuing education for teachers, they also depend on public policies built and implemented in each government. Currently, the pedagogical practices in the school are based on games and interactions and fields of experience, the child is the center of the educational process, the protagonist who participates, chooses, explores, contributes and plans together with the teachers, being respected in their cultural, social and ethnic diversity. As a final document, in addition to the dissertation, a documentary was made making it possible to see aspects of the history, but especially the practices in the institution's current context.